In the Eye of the Beholder: A Comparative Study of Public Morality and Free Speech Across the Pacific - Dermott, Terrence (Columbia Journal of Asian Law, 2013)
Most modern democracies have embraced some concept of freedom of expression in their system of jurisprudence. This right is not unfettered and the tension between free speech and societal norms is an ongoing legal question. Both Korean and American Courts have addressed the issue of what to do about expressions of sexuality and their place in the public square. However the two countries have different views as to what is obscene, and what to do about such material. These differences arise from different perceptions as to the natural order and what place government should play in people’s lives. These differences drive two of the world’s post-industrial democracies to travel parallel but separate legal paths.